Yersinia enterocolitica causing suppurative arthritis of the shoulder. Issue 8 (August 1994) - Tiddia, F; Cherchi, G B; Pacifico, L; Chiesa, C
Abstract : Yersinia enterocolitica is a rare cause of extra-intestinal disease. A case in a 60 year old butcher with hepatic cirrhosis who developed suppurative arthritis of the shoulder caused by Y enterocolitica is presented. There was no evidence of gastrointestinal infection or septicaemia. The severity of the illness was associated with various factors, including the underlying disease, the type of occupation, and the difficulties encountered in defining the optimal therapeutic regimen.